Dimethylarginines correlate to common carotid artery wall layer dimensions and cardiovascular risk factors in pregnant women with/without preeclampsia: A group comparative study. (March 2021) - Akhter, Tansim; Wikström, Gerhard; Larsson, Marita; Bondesson, Ulf; Hedeland, Mikael; Naessen, Tord
Highlights: Dimethylarginines associated to adverse effects on artery wall layer dimensions. Association in changes (pregnancy to postpartum) of arginines & artery wall layers. In line with documented increased risk of CVD later in life in preeclampsia. Abstract: Objectives: Asymmetric- and symmetric dimethylarginines (ADMA, SDMA) are elevated in cardiovascular disease (CVD). Preeclampsia is a pregnancy-specific syndrome and is an independent risk factor for subsequent CVD. Aims were to investigate whether ADMA, SDMA levels and l -arginine/ADMA and l -arginine/SDMA ratios during pregnancy and their changes from pregnancy to postpartum are associated to arterial wall layer dimensions and cardiovascular risk factors in women with and without preeclampsia. Study design: Dimethylarginines were analyzed by LC–MS, and the common-carotid-artery (CCA) intima and media thicknesses were estimated using 22-MHz non-invasive ultrasonography in women with preeclampsia (cases = 48) and normal pregnancies (controls = 58) in similar gestational age, with reassessment one-year postpartum. A thick intima, thin media and high intima/media ratio (I/M) indicates a less healthy arterial wall. Results: The median age of cases and controls was 30 years. During pregnancy, women with preeclampsia had higher plasma ADMA, SDMA and lower l -arginine/ADMA and l -arginine/SDMA (all p  < 0.01) than women with normal pregnancies. Further, ADMA, SDMA, l -arginine/ADMA and l -arginine/SDMA correlated to intima thickness ( rs  = 0.33/0.33/−0.33/−0.35 and p  < 0.01), I/M ( rs  = 0.26/0.28/−0.22/−0.26 and p  < 0.05) and mean arterial pressure (MAP) ( rs  = 0.43/0.42/−0.39/−0.40 and p  < 0.0001). Changes in ADMA, SDMA and l -arginine/SDMA from pregnancy to postpartum correlated to changes in intima thickness ( rs  = 0.22/0.32/-0.21 and p  < 0.05/<0.01/<0.05), I/M ( rs  = 0.22/0.31/0.08 and p  < 0.05/<0.01/=0.43) and MAP ( rs  = 0.31/0.53/-0.25 and p  < 0.01/<0.001/<0.05). No correlations were found for conventional CCA intima-media-thickness. Conclusions: Dimethylarginines were associated to signs of adverse effects on arterial wall layer dimensions and cardiovascular risk factors in women with and without preeclampsia, during pregnancy and to their changes from pregnancy up to one-year postpartum.